Investigation of Photocatalyst Composites for Pollutant Degradation in a Microslit Reactor Utilizing High Throughput Screening Techniques. Issue 11 (16th November 2022) - Engelhardt, Tony B.; Schmitz‐Stöwe, Sabine; Schwarz, Thomas; Stöwe, Klaus
Abstract: The high‐throughput screening investigations on TiO2 based photocatalyst composites presented here have been carried out in a 60‐fold parallel photoreactor. Additional catalyst testing was performed in a microslit reactor system with immobilized catalysts. For further enhancing the photocatalytic activity of TiO2 (P25), composites of P25 and, for example, Bi2 O3, CeO2, g‐C3 N4, WO3 or ZnO were formulated in different nominal molar ratios. The catalysts' performances were assessed by their conversion of 17α‐ethinyl estradiol (EE2) in aqueous solutions, determined by LC–MS. Findings show rapid EE2 conversions in short residence times. The extensive testing of catalysts led to the conclusion that the photocatalytic conversion is rather a function of residence time than a function of the materials utilized. This makes adequate process development seem more important than material development. The novelty of this contribution lies in the unique combination of testing a wide range of composite catalysts in a unique microreactor geometry. Abstract : Heterojunction photocatalysis could be a valuable addition to existing waste water purification techniques. This article provides a novel approach on photocatalyst research utilizing high throughput techniques and a microslit reactor with strong application relation. Results show that this new reactor type allows for rapid degradation of the micro‐pollutant 17α‐ethinyl estradiol.